2019
DOI: 10.3390/cells8070757
|View full text |Cite
|
Sign up to set email alerts
|

The IL4I1 Enzyme: A New Player in the Immunosuppressive Tumor Microenvironment

Abstract: The high metabolic needs of T lymphocytes in response to activation make them particularly vulnerable to modifications of their biochemical milieu. Immunosuppressive enzymes produced in the tumor microenvironment modify nutrient availability by catabolizing essential or semi-essential amino acids and producing toxic catabolites, thus participating in the local sabotage of the antitumor immune response. L-amino-acid oxidases are FAD-bound enzymes found throughout evolution, from bacteria to mammals, and are oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 40 publications
1
52
0
Order By: Relevance
“…Finally, RNAseq also unraveled expression changes of certain newly-discovered genes in response to influenza infection of the upper airway cells. Genes such as HEATR9 [23], IL4I1 [24], TNFSF13B ( BAFF ) [25], and PDCD1 ( PD-1 ) [26] are recently implicated in influenza pathogenesis and mucosal defense, thereby signifying the role of the nasal epithelium against influenza infection. Furthermore, RNAseq identified altered expression of ART3 and KCNH7 genes that were not previously detected in influenza transcriptomes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, RNAseq also unraveled expression changes of certain newly-discovered genes in response to influenza infection of the upper airway cells. Genes such as HEATR9 [23], IL4I1 [24], TNFSF13B ( BAFF ) [25], and PDCD1 ( PD-1 ) [26] are recently implicated in influenza pathogenesis and mucosal defense, thereby signifying the role of the nasal epithelium against influenza infection. Furthermore, RNAseq identified altered expression of ART3 and KCNH7 genes that were not previously detected in influenza transcriptomes.…”
Section: Discussionmentioning
confidence: 99%
“…The gene coding for the amine oxidase “Interleukin 4 Induced 1” (IL4I1) was strongly down-regulated (30-fold) 4h after infection with PEDV. Besides catalysis of L-Phenylaniline into Phenylpyruvate (Fig.3), IL4I1 also fulfills an important role in signaling in “synaptic clefts” formed between antigen presenting cells (APC) and T cells (so-called “immune cleft”: see also below)(30: Boulland et al 2007, 31: Molinier-Frenkel et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…data provided in the GeneCards reports of these genes/proteins. The drawing was inspired by figures presented in the publications of Molinier-Frenkel et al (31:2019) and Sattentau (32: 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mainly produced by macrophages and dendritic cells (DCs) in the context of pro-T helper type 1 (Th1) inflammatory stimuli (3). IL4I1 is particularly abundant in the tumor microenvironment of inflammatory human cancers and may be associated with a poor prognosis [reviewed in (4)]. Indeed, murine models have shown that IL4I1 negatively regulates the expansion and functionality of antitumor CD8 + T cells (5,6), an effect that has been confirmed by the analysis of human primary cutaneous melanomas (7).…”
Section: Introductionmentioning
confidence: 99%